Overview of Maternal Pregnancy History in Stunted Toddlers - Putri, Novita Amalia Fatma; Susanti, Yulia; Santoso, Dona Yanuar Agus; Jati, Riani Pradara (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Stunting or short stature is a condition of impaired growth and development in infants and toddlers caused by chronic malnutrition, resulting in the child being too short for their age. The prevalence in Kendal Regency has decreased, but it has not yet met the target. Objective to describe the maternal pregnancy history of children with stunting. This is a quantitative study using a retrospective approach. The population in this study consists of mothers with toddlers experiencing stunting, located in the stunting locus health centers in Kendal Regency, totaling 680 individuals. The sample was selected using a purposive technique with a cluster sampling approach, with a total sample size of 251 participants. The characteristics of the respondents show that the average age of the mothers is 28 years, with 115 mothers (45.8%) having a high school education. The majority of mothers are unemployed or housewives, totaling 110 (43.8%). Male toddlers account for 132 (52.6%) of the sample, and 132 (52.6%) of the mothers have toddlers classified as severely stunted. The maternal pregnancy history reveals that the majority, 233 (92.8%), are at risk due to factors such as pregnancy spacing, body stature, pregnancy planning, iron (Fe) supplement intake, nutritional intake, prenatal checkups, pregnancy-related hypertension, anemia during pregnancy, pregnancy contractions, and rest patterns.